Crisis communication: Fake news and informative follow-up on the Galician fire wave in October 2017 - Conde Vázquez, Erica (Revista Española de Comunicación en Salud, 2019)
Between Friday, October 13 and Monday afternoon, October 16, 2017, one hundred and forty-six fires were registered in Galicia. Sixty on Sunday and twenty-eight of these initiates at dawn, between midnight and nine in the morning. Leaving a balance of four fatalities and some twenty wounded and a challenge for the media coverage of the media, specifically in its function of keeping the citizen informed in emergency situations. Therefore, the analysis of the information treatment in two newspapers, one of national coverage and another of regional coverage, analyzing the follow-up and content of its news, as well as compliance with the decalogue of recommendations for media and journalist of catastrophe events issued by the Colexio of Xornalistas. In addition, special consideration will be given to the fact that the aforementioned media incur the disclosure of Fake News during the event.
Keywords: fake news; postruth; crisis management; forest fires; mass media